Forage availability and quality on grazing reserve along the waterways for livestock production at Tanjung Agas, Ledang, Johor - Yusof, Muhammad Helmi Izzuddin (2016)
The waterways along Tanjung Agas approximately 10km length, also used as grazing area. The purpose of this study is enable to identify the potential of this area and boost the development into larger livestock production. The general objective of the study is to evaluate the availability of vegetation and its quality to support livestock production at the grazing reserve along the waterways. The specific objectives of the study firstly are to identify the available vegetation along the waterways uses for livestock feeding, secondly are to determine the production and nutrient content of the forages grazed by livestock at patched and non-patched area of urine and dung forages, and thirdly are to quantify the population of livestock grazed on the studied area. Along the waterway, all types of plant either it was grasses, legumes, palatable plants was observed and identified. The documentation and classification of existing vegetation along the waterways, via observation, taken their pictures and further identified by their morphology and classified them. The most abundant palatable forages are Axonopus compressus, Imperata cylindrica and Paspalum conjugatum. The most abundant of non-palatable plants are Acanthus ilicifolius, Morinda citrifolia and Acacia mangium. Knowing the forage dry matter yield is important when making decisions about crop productivity, fertility, feeding, grazing schemes and stocking rates. The land area calculated was 10 km length and 30 meters width, was equivalent 10 hectares. The average dry matter (DM) content of the forages is 39.74 %. The forages dry matter yield at both area was calculated, the average dry matter yield of forages was 470.4 kg DM per ha. The 20 days intervals of regrowth period given to each location at patched area was 0.23 g/ day, whereas the average growth rate of the forages at non-patch area was 0.22 g/ day. The chemical analysis of forages, the Crude Protein (CP) content for patched sites was 10.84%, whereas non-patched area was 8.64%. The chemical test showing that patched sites where CP, Ash and Acid Detergent Lignin (ADL) were significantly different (P< 0.05) to non-patched site. Whereas, DM, Acid Detergent Fiber (ADF), Neutral Detergent Fiber (NDF) and Crude Fiber was not significant different (P< 0.05) to non-patched site. Total cattle population were 48 head with different production levels which is Kedah-Kelantan cross and Brahman cross breed, and the total goat population calculated were 41 head with different production levels which is Katjang and Jamnapari cross breed. The livestock performance in relation to the palatable plant species regrowth rate throughout along the study area was not enough for the study area was not enough to meet livestock dry matter intake requirement daily. In conclusion, this study clearly shows that this area has high potential to be utilized as ruminant farming corporation between local farmers because of large planting area can be used for replant improved grasses species to sustain the livestock growth because of available palatable plant species was not sufficient to be used as main feed source for the currently total amount of grazing livestock, by improving in term of forages quality and facility, this land area suitable to be utilized as semi-intensive or extensive farming system.